Hydroclimatic shifts in northeast Thailand during the last two millennia – the record of Lake Pa Kho. (1st March 2015) - Chawchai, Sakonvan; Chabangborn, Akkaneewut; Fritz, Sherilyn; Väliranta, Minna; Mörth, Carl-Magnus; Blaauw, Maarten; Reimer, Paula J.; Krusic, Paul J.; Löwemark, Ludvig; Wohlfarth, Barbara
Abstract: The Southeast Asian mainland is located in the central path of the Asian summer monsoon, a region where paleoclimatic data are still sparse. Here we present a multi-proxy (TOC, C/N, δ 13 C, biogenic silica, and XRF elemental data) study of a 1.5 m sediment/peat sequence from Lake Pa Kho, northeast Thailand, which is supported by 20 AMS 14 C ages. Hydroclimatic reconstructions for Pa Kho suggest a strengthened summer monsoon between BC 170–AD 370, AD 800–960, and after AD 1450; and a weakening of the summer monsoon between AD 370–800, and AD 1300–1450. Increased run-off and a higher nutrient supply after AD 1700 can be linked to agricultural intensification and land-use changes in the region. This study fills an important gap in data coverage with respect to summer monsoon variability over Southeast Asia during the past 2000 years and enables the mean position of the Intertropical Convergence Zone (ITCZ) to be inferred based on comparisons with other regional studies. Intervals of strengthened/weaker summer monsoon rainfall suggest that the mean position of the ITCZ was located as far north as 35°N between BC 170–AD 370 and AD 800–960, whereas it likely did not reach above 17°N during the drought intervals of AD 370–800 and AD 1300–1450. The spatial pattern of rainfall variation seems to have changed after AD 1450, when the inferred moisture history for Pa Kho indicates a more southerly location of the mean position of the summer ITCZ. Highlights: New high-resolution 14 C-dated, multi-proxy peat sequence from NE Thailand. Reconstruction of hydroclimatic variability during the past 2000 years. Strengthened Asian summer monsoon BC 170–AD 370 and AD 800–970. Weaker Asian summer monsoon AD 370–800 and AD 1300–1450. Shifts in the mean position of the summer ITCZ during the past 2000 years.